2019
DOI: 10.1109/tit.2019.2938171
|View full text |Cite
|
Sign up to set email alerts
|

A General Formula for the Stationary Distribution of the Age of Information and Its Application to Single-Server Queues

Abstract: This paper considers the stationary distribution of the age of information (AoI) in information update systems. We first derive a general formula for the stationary distribution of the AoI, which holds for a wide class of information update systems. The formula indicates that the stationary distribution of the AoI is given in terms of the stationary distributions of the system delay and the peak AoI. To demonstrate its applicability and usefulness, we analyze the AoI in single-server queues with four different… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
138
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(158 citation statements)
references
References 21 publications
2
138
0
3
Order By: Relevance
“…We showed that determinacy in packet generation and/or service does not necessarily minimize age. Similar results were independently obtained in [35].…”
Section: Introductionsupporting
confidence: 89%
“…We showed that determinacy in packet generation and/or service does not necessarily minimize age. Similar results were independently obtained in [35].…”
Section: Introductionsupporting
confidence: 89%
“…The service time is distributed as a memoryless exponential random variable with mean µ, which is dependent on the computation service time. This tandem queue model is inspired by packet management schemes in [3], [5]. The first queue is in M/GI/1/1 form while the second queue is in GI/M/1/2* form or equivalently non-preemptive last come first serve with discarding.…”
Section: The Tandem Queue Modelmentioning
confidence: 99%
“…After the pioneering works [1], [2] that analyze queuing models motivated from vehicular status update systems, the AoI metric has been found useful in various scenarios. [3], [4] investigate the role of packet management to decrease the AoI while [5] provides a general AoI analysis in various preemptive and non-preemptive queuing disciplines coming after earlier works such as [6], [7]. References [8]- [17] consider AoI in energy harvesting communication systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, while interesting, these works do not 1 An interested reader may refer to [17] and [18] for a comprehensive survey and references on AoI. 2 Therefore, considering the AoI violation in this work is a different measure compared to the peak-AoI violation [23] consider controlling the tail of AoI violation distribution.…”
Section: Introductionmentioning
confidence: 99%